Identifikasi Profil Pelanggan Restoran berdasarkan Variabel Lifestyle dengan Activities, Interest, and Opinion (AIO) Approach - Jihan Putri Nabilah; Hasrini Sari (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2023)
This study aims to identify market segments from existing customers of a restaurant in Bintaro, South Tangerang. This study will use the activity, interest, and opinion (AIO) model to identify market segments from existing customers. The aim is to find out the lifestyle of the restaurant's existing customers. Data collection in this study used a questionnaire, based on AIO statements with answers on a scale of 1-5. Before the questionnaire is used for the data collection process, the steps that need to be carried out are testing the validity and reliability of the questionnaire. This is necessary to ensure the quality of the questionnaire. The data collection process managed to collect as many as 1401 respondents and during the initial data testing process there was one data that was indicated as an outlier so that as many as 140 data could be processed. The collected data will be analyzed using a hierarchical cluster method. Based on the data collected, there are four clusters with different characteristics. The first cluster is referred to as effective millennials, while the second cluster is referred to as family women, the third cluster is referred to as sports persons, and the fourth cluster is referred to as family persons. The four cluster names are based on cross-tabulation analysis of the demographic variables in the questionnaire and statistical inference using the ANOVA test to determine which AIO dimension has the highest average.